(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Symptoms of intoxication in acute paraproctitis are one of the most common complaints among proctological diseases. Acute paraproctitis is an acute inflammation of the perirectal rectum, an inflammatory process arising from the anal crypts and anal glands. In 2023, in the clinic named of Rustamov, 50 patients with acute paraproctitis intoxication were studied and underwent surgery. According to the anatomical localization of the primary disease in patients, it manifests itself in different clinical manifestations. Almost all patients showed acute paraproctitis pain. Patients with subcutaneous proctitis complain of perianal discomfort and itching. The pain is often caused by increased pressure on the perineum from sitting or defecation. In acute paraproctitis, symptoms of intoxication such as fever, chills were observed in most patients. We divided the examined patients into 3 groups according to the degreeof intoxication. Blood leukocyte intoxication index (LII) was calculated according to the Kalf-Kalif formula.